2007
DOI: 10.1111/j.1365-2036.2007.03302.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis progression occurs in a subgroup of heavy drinkers with typical histological features

Abstract: SUMMARY BackgroundStudies using consecutive liver biopsies constitute an attractive approach to gaining insight into the pathogenesis of alcoholic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 30 publications
3
72
1
6
Order By: Relevance
“…In the study by Orrego et al, there was a clear increase in mortality in those with histological features of 'hepatitis'. Others have also shown that the presence of ASH on biopsy is an independent predictor of progression of fibrosis and development of cirrhosis in patients with alcoholic liver disease, [34] albeit in our study, there was no significant association between degree of fibrosis and nodule formation and short-term outcome. However, the prognostic implications of our results need to be interpreted cautiously given the relatively small sample size of biopsies assessed in this study.…”
Section: Discussioncontrasting
confidence: 83%
“…In the study by Orrego et al, there was a clear increase in mortality in those with histological features of 'hepatitis'. Others have also shown that the presence of ASH on biopsy is an independent predictor of progression of fibrosis and development of cirrhosis in patients with alcoholic liver disease, [34] albeit in our study, there was no significant association between degree of fibrosis and nodule formation and short-term outcome. However, the prognostic implications of our results need to be interpreted cautiously given the relatively small sample size of biopsies assessed in this study.…”
Section: Discussioncontrasting
confidence: 83%
“…Thus, variables known to be potential risk factors for ALD fibrosis/cirrhosis were included regardless of statistical significance in univariate analysis. Steatosis was categorized using the median value of 15% as a cut-off, a value close to that previously reported (10%) as a risk factor for fibrosis progression in ALD [10]. The Hosmer-Lemeshow test was used to verify goodness of fit of the model to the data (a non-significant result was indicative of satisfactory calibration).…”
Section: Endpoints and Statistical Analysismentioning
confidence: 99%
“…While the threat of cirrhosis increases in proportion to daily alcohol consumption, with the highest risk found above 120 g/day [5], the causal association has been only partially unraveled, since 10-20% of heavy drinkers ultimately develop liver cirrhosis [6]. It is recognized that other factors, including gender [7], insulin resistance, body mass index (BMI), steatosis [8][9][10], and environmental factors, such as chronic viral infection [11], play a role in the genesis of alcohol-induced liver fibrosis. Nevertheless, these factors fail to explain the extreme variability in ALD progression.…”
Section: Introductionmentioning
confidence: 98%
“…A heavy binge drinking episode in patients who chronically consume alcohol is the most common trigger for the admission of patients with steatohepatitis [72] . A study of a large cohort of drinkers with consecutive biopsies suggested the concept of multiple hits of alcoholic hepatitis in the same patients as the prime determinant in the progression of alcoholic liver injury [73] . Mathews et al [74] have recently developed a chronic plus binge alcohol feeding model in mice, which is similar to the drinking patterns of many alcoholic hepatitis patients: A history of chronic drinking and recent excessive alcohol consumption have begun to identify novel mechanisms that participate in the pathogenesis of alcoholic liver injury.…”
Section: Effect On the Livermentioning
confidence: 99%